Evaluasi Pakan Daun Ubi Jalar dan Daun Singkong pada Kualitas Telur Itik yang Disimpan pada Suhu 5°C - Tera Fit Rayani; Sumiati, Sumiati; Darmawan, Arif (Jurnal Ilmu Pertanian Indonesia, 2022)
Egg yolks contain omega-3 and omega-6 fatty acids that are easily oxidized during storage, so they must be protected. The objective of this study was to evaluate the effect of feeding containing sweet potato leaves meal (TDU) and cassava leaves meal (TDS) on the quality of duck eggs stored at 5 °C for 8 weeks. This study used a completely randomized design, 6 ´ 3 factorial design with 4 replications. Factor A was feed treatment (R0 = control feed without TDU or TDS; R1 = feed containing 0% TDU and 10% TDS; R3 = feed containing 5% TDU and 0% TDS; R4 = feed containing 5% TDU and 5% TDS; R5 = f eed containing 5% TDU and 10% TDS). Factor B was egg storage time (0, 4, and 8 weeks). A total of 144 duck eggs were used in this study. The results showed no interaction between the supplementation of TDU and TDS with the storage time on the quality of stored eggs. Supplementation of TDU or TDS or their combination significantly (p